Survival of Phytophthora colocasiae in Field Soil at Various Temperatures and Water Matric Potentials - Quitugua, R J (Plant disease, 1998)
A large number of the zoosporangia of Phytophthora colocasiae incorporated into moist soils germinated by zoospore discharge, and/or lysed in the soil during the first 5 days of incubation, decreasing the initial number of colony-forming units from 1 × 104 to 1 × 102 per g of soil in all treatments. Eighteen days after incorporation, the viable zoosporangia present in moist soils had thickened their cell walls and germinated only directly, often producing smaller zoosporangia. A few thick-walled chlamydospores were observed, and they germinated only directly. Zoosporangia in soils at -1,500 J/kg matric potential survived longer than 107 days, and the amount of viable Zoosporangia present at that time was approximately 0.1 × 102 CFU/g of soil. Apparently the great majority of the thin-walled zoosporangia produced on V8 agar, when incorporated into moist soil, germinated indirectly in the first 5 days of incubation. Zoosporangia that did not germinate became resting zoosporangia by increasing their wall thickness or by producing chlamydospores. These enabled the pathogen to survive in soil at -1,500 J/kg matric potential for more than 3 months. However, in the absence of the host, the pathogen is predicted to survive less than 1 year due to its lack of saprophytic ability to colonize nonhost tissues